GRASP55 regulates intra‐Golgi localization of glycosylation enzymes to control glycosphingolipid biosynthesis. (13th September 2021) - Pothukuchi, Prathyush; Agliarulo, Ilenia; Pirozzi, Marinella; Rizzo, Riccardo; Russo, Domenico; Turacchio, Gabriele; Nüchel, Julian; Yang, Jia‐Shu; Gehin, Charlotte; Capolupo, Laura; Hernandez‐Corbacho, Maria Jose; Biswas, Ansuman; et al.
Abstract: The Golgi apparatus, the main glycosylation station of the cell, consists of a stack of discontinuous cisternae. Glycosylation enzymes are usually concentrated in one or two specific cisternae along the cis‐trans axis of the organelle. How such compartmentalized localization of enzymes is achieved and how it contributes to glycosylation are not clear. Here, we show that the Golgi matrix protein GRASP55 directs the compartmentalized localization of key enzymes involved in glycosphingolipid (GSL) biosynthesis. GRASP55 binds to these enzymes and prevents their entry into COPI‐based retrograde transport vesicles, thus concentrating them in the trans ‐Golgi. In genome‐edited cells lacking GRASP55, or in cells expressing mutant enzymes without GRASP55 binding sites, these enzymes relocate to the cis ‐Golgi, which affects glycosphingolipid biosynthesis by changing flux across metabolic branch points. These findings reveal a mechanism by which a matrix protein regulates polarized localization of glycosylation enzymes in the Golgi and controls competition in glycan biosynthesis. SYNOPSIS: How the compartmentalized localization of glycosylation enzymes in Golgi is achieved and how it regulates glycosylation is incompletely understood. Here, GRASP55 is found to control competition between glucosylceramide synthase (GCS) and sphingomyelin synthase 1 (SMS1), two enzymes of the glycosphingolipid (GSL) biosynthetic pathway, by regulating trans ‐Golgi localization of GCS. SMS1 and GCS localize to the trans ‐Golgi, where they compete for the shared substrate ceramide. GRASP55 binding to the C‐terminus of GCS prevents its sorting into retrograde COPI vesicles, thus localizing GCS to the trans ‐Golgi. Absence of GRASP55‐GCS interaction relocates GCS to the cis ‐Golgi, while SMS1 remains in the trans ‐Golgi. GCS in the cis ‐Golgi may have preferential access to ceramide compared to SMS1. Preferential GCS access results in increased glycosphingolipid biosynthesis in the absence of GRASP55. Abstract : Intra‐Golgi compartmentalization of glucosylceramide synthase (GCS) and lactosylceramide synthase 1 (LCS1) depends on their binding to matrix protein GRASP55, which prevents their sorting into retrograde COPI vesicles.